2015
DOI: 10.3390/bs5020176
|View full text |Cite
|
Sign up to set email alerts
|

Resilience in Physically Abused Children: Protective Factors for Aggression

Abstract: Aggression continues to be a serious problem among children, especially those children who have experienced adverse life events such as maltreatment. However, there are many maltreated children who show resilient functioning. This study investigated potential protective factors (i.e., child prosocial skills, child internalizing well-being, and caregiver well-being) that promoted positive adaptation and increased the likelihood of a child engaging in the healthy, normative range of aggressive behavior, despite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 58 publications
1
41
0
1
Order By: Relevance
“…This was consistent with previous study of Milot et al [30] who found a significant relation between maltreatment and development of externalizing problems in 3 to 6 years old children raised in economically disadvantaged families. In addition, Holmes et al [31] revealed that children who were physically abused were 1.5 times more likely to demonstrate clinical levels of aggressive act relative to children who were not physically abused. The study suggested that early behavioral adaptations could determine either enhanced or disrupted behavioral functioning during later life.…”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with previous study of Milot et al [30] who found a significant relation between maltreatment and development of externalizing problems in 3 to 6 years old children raised in economically disadvantaged families. In addition, Holmes et al [31] revealed that children who were physically abused were 1.5 times more likely to demonstrate clinical levels of aggressive act relative to children who were not physically abused. The study suggested that early behavioral adaptations could determine either enhanced or disrupted behavioral functioning during later life.…”
Section: Discussionmentioning
confidence: 99%
“…Searching for those protective factors acting at different stages of the model, such as cognitive reappraisal, self‐control, cognitive control, or well‐being, has been the focus of a number of research studies (Bates, Archer, & Graham‐Kevan, ; Denson, ; Gutiérrez‐cobo, Cabello, & Fernández‐berrocal, ; Holmes, Yoon, Voith, Kobulsky, & Steigerwald, ). Previous studies have found two relevant variables acting as risk and protective factors of aggression, respectively, negative affect (NA) and emotional intelligence (EI).…”
Section: Introductionmentioning
confidence: 99%
“…Child behavior problems have been investigated by many researchers in developed countries. A large body of literature provides empirical support for the hypothesis that factors other than the children themselves are responsible for behavior problems; these factors include dysfunctional parenting, maltreatment, an adverse relationship between the child's mother and father, and high stress in the parents . Dysfunctional parenting, such as harsh or excessively lax discipline, is significantly associated with CBP .…”
mentioning
confidence: 99%
“…A large body of literature provides empirical support for the hypothesis that factors other than the children themselves are responsible for behavior problems; these factors include dysfunctional parenting, maltreatment, an adverse relationship between the child's mother and father, and high stress in the parents. [7][8][9][10][11][12][13][14] Dysfunctional parenting, such as harsh or excessively lax discipline, is significantly associated with CBP. 15 This dysfunctional parenting aggravates CBP, which are likely to increase over time.…”
mentioning
confidence: 99%